2018
DOI: 10.1001/jamaoncol.2018.2078
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Lung Cancer Risk on the Basis of a Biomarker Panel of Circulating Proteins

Abstract: This study provided a proof of principle in showing that a panel of circulating protein biomarkers may improve lung cancer risk assessment and may be used to define eligibility for computed tomography screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 16 publications
(30 reference statements)
3
87
2
1
Order By: Relevance
“…Luminex analyses of fresh blood samples also revealed that of three previously established biomarkers of lung cancer risk, i.e., CEA, CA125, CYFRA 21-1 19 , only CEA was higher in smokers. Interestingly, Pearson correlation analyses (Table 2) revealed that CEA levels correlated with monocyte (R = 0.463) and granulocyte (R = 0.505) numbers.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Luminex analyses of fresh blood samples also revealed that of three previously established biomarkers of lung cancer risk, i.e., CEA, CA125, CYFRA 21-1 19 , only CEA was higher in smokers. Interestingly, Pearson correlation analyses (Table 2) revealed that CEA levels correlated with monocyte (R = 0.463) and granulocyte (R = 0.505) numbers.…”
Section: Discussionmentioning
confidence: 64%
“…As well, since a panel of biomarkers consisting of CEA, CA125, CYFRA 21-1 and Pro-SFTPB was recently found to be highly predictive of smokers subsequently developing lung cancer 19 , we were interested in determining their values. We did not test SFTPB, however, since there were no commercially available kits and it had been reported that SFTPB has a non-linear, J-shaped association with lung cancer risk (with no and high levels increasing risk), making interpretation of results difficult 23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrated classifiers have also been explored in terms of plasma protein biomarkers such as the ones tested by some panel components in our cohort (25).…”
Section: Discussionmentioning
confidence: 99%
“…Another study detected a combined panel of circulating tumour DNA fragments and tumour-related proteins: 59% of newly diagnosed lung-cancer cases were uncovered with high specificity, but lower sensitivity for early-stage cancers [ 67 ]. More recently, a risk-prediction model based on smoking history and immunodetection of four protein markers (cancer antigen 125, carcinoembryonic antigen, cytokeratin-19 fragment, and precursor of surfactant protein B) in US cohorts was found to outperform a smoking-history-only model when applied to pre-diagnostic samples from two European cohorts [ 68 ]. At a fixed specificity of 0.83 based on the screening criteria of the United States Preventive Services Task Force (USPSTF), the model based on smoking-plus-biomarker had a sensitivity for screening eligibility of 0.63 vs. 0.42 for the smoking-based model alone.…”
Section: Eligibly Criteria For Ldct-lcsmentioning
confidence: 99%